Analisis Variasi Coil Spring Terhadap Kecepatan Getaran - Prabu Wiwit Laksono; Listiyono Listiyono (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2024)
Vibration in the vehicle body is an important factor that needs to be considered when using a vehicle. This is important because vibration can affect driving comfort and safety, both for the driver and passengers. The less vibration there is, the more comfortable the vehicle is to drive and ride. The aim of this research is to determine the variation of the coil spring on vibration speed. In this research, the approach used is quantitative with an experimental type. The independent variables include variations in coil spring diameter, namely 9 mm, 11 mm, and 13 mm, as well as coil spring length, namely 130 mm, 180 mm, and 230 mm. The dependent variable analyzed is vibration speed. Data was obtained using a coil spring load test tool and a Vibration meter to measure vibration speed. The research results show that the interaction between the diameter and length of the coil spring influences the vibration speed. The highest vibration speed was found in the coil spring with a diameter of 9 mm and a length of 230 mm, while the lowest vibration speed occurred at a diameter of 13 mm and a length of 130 mm. An interaction with a diameter of 13 mm and a length of 130 mm indicates the optimal coil spring size.